Yield and sucrose losses in sugarbeet due to root rot - V.N. PATHAK, SHIM SEN SHARMA and (Indian Phytopathology, 2002)
An increase in disease incidence caused a corresponding decrease in root yield. Yield reductions of 46.5 and 62.2 per cent were recorded with PCNS in 1982-83 and 1983-84, respectively. Infection of more than 10 per cent root area caused significant (p = 0.05) decrease in sucrose content of beet root as compared to healthy roots. Almost complete loss (99.9%) of sucrose was record cd when infected root area was more than 80 per cent.